2013
DOI: 10.1111/hepr.12122
|View full text |Cite
|
Sign up to set email alerts
|

First successful case of simultaneous liver and kidney transplantation for patients with chronic liver and renal failure in Japan

Abstract: Establishment of a preferential liver allocation rule for simultaneous liver and kidney transplantation (SLK) and revisions of laws regarding organ transplants from deceased donors have paved the way for SLK in Japan. Very few cases of SLK have been attempted in Japan, and no such recipients have survived for longer than 40 days. The present report describes a case of a 50-year-old woman who had undergone living donor liver transplantation at the age of 38 years for management of post-partum liver failure. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…In addition, because SLK practice varies worldwide, the results of our study would be helpful for centers in other countries to consider expansion of SLK criteria. The new UNOS SLK policy contains more aggressive indication criteria than other countries’ or regions’ policies . To confirm the validity and applicability of the new UNOS SLK policy, additional national or international surveys and/or multisite studies are needed .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, because SLK practice varies worldwide, the results of our study would be helpful for centers in other countries to consider expansion of SLK criteria. The new UNOS SLK policy contains more aggressive indication criteria than other countries’ or regions’ policies . To confirm the validity and applicability of the new UNOS SLK policy, additional national or international surveys and/or multisite studies are needed .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, there was no case that underwent SLK for PKD. Additionally, the first case of successful SLK was reported in 2013 in Japan . In the current Japanese status, it is difficult to perform SLK even with renal failure, because most transplantation cases are dependent on a living donor.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the first case of successful SLK was reported in 2013 in Japan. 33 In the current Japanese status, it is difficult to perform SLK even with renal failure, because most transplantation cases are dependent on a living donor. On the other hand, Simpson et al reported that SLK has an immunological advantage over serial transplantation in terms of avoiding the risk of pre-sensitization, when recipients require liver and kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The recipient surgery included conventional orthotopic liver transplantation with the removal of the native liver with the retrohepatic inferior vena cava. Both the left axillary and the right saphenous veins were exposed for veno‐venous bypass during the anhepatic phase . Explantation of the native liver began with the division of the hepatic hilum, especially division of the distended hepatic artery that was hemorrhagic due to portal hypertension.…”
Section: Case Reportmentioning
confidence: 99%
“…Both the left axillary and the right saphenous veins were exposed for veno-venous bypass during the anhepatic phase. 17 Explantation of the native liver began with the division of the hepatic hilum, especially division of the distended hepatic artery that was hemorrhagic due to portal hypertension. After dissection of the hepatic artery and the common bile duct, the left and right lobes were dissected from the surrounding adhesion, which was also hemorrhagic.…”
Section: Transplant Surgerymentioning
confidence: 99%